Persepsi Manajer Mengenai Pengaruh Kinerja Komite Audit Dan Efektifitas Audit Internal Terhadap Pencegahan Fraud (Studi Empiris Pada Lembaga Perbankan Di Kota Ambon) - Dwitantri, Adysti; Gasperz, Jefry; Hehanussa, Salomi Jacomina (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This study aims to determine the effect of audit committee performance and internal audit effectiveness on fraud prevention from the perception of managers at banking institutions in Ambon City. This research strategy uses quantitative methods with a descriptive approach. The population in this study is banking institutions in Ambon City with a research sample of 33 respondents, namely managers related to internal audit practices and audit committees. Data collection uses a questionnaire method distributed to respondents, namely the manager level who has attended audit/corporate governance/fraud training. The results prove that audit committee performance and internal audit effectiveness have a significant effect on fraud prevention. If the two variables of audit committee performance and internal audit effectiveness are in accordance with their respective standards, it will be good at preventing fraud as expected in banking institutions